Chitin-enriched insect frass fertilizer as a biorational alternative for root-knot nematode (Meloidogyne incognita) management - Kisaakye, James; Beesigamukama, Dennis; Haukeland, Solveig; Subramanian, Sevgan; Thiongo, Paul K.; Kelemu, Segenet; Tanga, Chrysantus M. (Frontiers in Plant Science, 2024)
Root knot nematodes (Meloidogyne spp.) are serious pests for most food crops, causing up to 100% yield loss. Yet, commercial nematicides are costly and harmful to the environment. While the nematicidal potential of crustacean and synthetic chitin has been demonstrated globally, research on the potential of insect-derived chitin for nematode control has received limited attention. Here, seven chitin-fortified black soldier fly frass fertilizer extracts (chFE) were assessed for their suppressiveness of M. incognita and impacts on spinach growth in comparison with a commercial nematicide, using in vitro and in vivo bioassays. The performance of chFE and control treatments were assessed by determining effect on nematode egg hatchability, infective juvenile (J2) mortality and paralysis, number of galls, egg masses and J2s per plant, and spinach root and shoot biomass. In vitro results showed that chFE and commercial nematicide suppressed nematode egg hatchability by 42% and 52%, respectively, relative to the control (sterile distilled water). Up to 100% paralysis was achieved when M. incognita J2s were exposed to either chFE or commercial nematicide. Further, the J2 mortality achieved using chFE (95%) was comparable to the value achieved using commercial nematicide (96%); in all treatments, mortality increased with exposure time. Similarly, up to 85% suppression of gall development was achieved when spinach plants were grown in soil drenched with chFE; up to 79% reduction in egg mass formation and 68% suppression of J2 development in the root system was achieved using chFE. Also, chFE application significantly increased spinach root and shoot biomass by 54 -74% and 39 -58%, respectively, compared to the commercial nematicide. Our findings demonstrate the nematicidal potential of chFE and benefits on crop production. Thus, chFE could be considered as a promising multipurpose, regenerative and cost-effective input for sustainable management of plant-parasitic nematodes and enhancement of crop yield.